Simplify -3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3) answer choices are: A. 1 - 7p - 2p2 + 5p3 B. 5p3 - 2p2 - 7p + 1 C. 1 + 7p + 2p2 - 5p3 D. -5p3 + 2p2 + 7p + 1

Question|Rated bad

Asked 6/21/2011 7:08:43 AM

Updated 6/29/2014 1:44:47 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/29/2014 1:43:33 AM]

xramen135@aol.com|Points 440|

Expert answered|xramen135@aol.com|Points 440|

Question|Rated bad

Asked 6/21/2011 7:08:43 AM

Updated 6/29/2014 1:44:47 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/29/2014 1:43:33 AM]

Rating

3

-3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3)

= 5p^3 - 2p^2 - 7p + 1

= 5p^3 - 2p^2 - 7p + 1

Added 6/29/2014 1:43:29 AM

This answer has been confirmed as correct and helpful.

3

(5m + 2n) + (n - 3m) + (7 - 3n)

= (3n + 2m) + (7 - 3n)

= 2m + 7

= (3n + 2m) + (7 - 3n)

= 2m + 7

Added 6/29/2014 1:44:47 AM

This answer has been confirmed as correct and helpful.

Factor -x2y2 + x4 + 9y2 - 9x2

Question

Expert Answered

Updated 6/11/2014 12:39:37 AM

2 Answers/Comments

-x^2y^2 + x^4 + 9y^2 - 9x^2

= x^2(x^2 - y^2) - 9(x^2 - y^2)

= (x^2 - y^2)(x^2 - 9)

= (x + y)(x - y)(x + 3)(x - 3)

= x^2(x^2 - y^2) - 9(x^2 - y^2)

= (x^2 - y^2)(x^2 - 9)

= (x + y)(x - y)(x + 3)(x - 3)

Added 6/11/2014 12:38:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/11/2014 12:55:28 AM]

(5x2 + 2x - 3)(x - 1) answer choices are: A. 5x - 2x2 + 3x4
B. 5x2 - 5x - 1
C. 7x3 + 6x2 - 1x
D.5x3 - 3x2 - 5x + 3 **Weegy:** D. Please rate the answer. (More)

Question

Expert Answered

Updated 310 days ago|1/9/2018 4:58:38 AM

1 Answer/Comment

(5x^2 + 2x - 3)(x - 1)

= 5x^3 + 2x^2 - 3x - 5x^2 - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 + 2x^2 - 3x - 5x^2 - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 310 days ago|1/9/2018 4:58:38 AM

This answer has been confirmed as correct and helpful.

(5x2 + 2x - 3)(x - 1)

Question

Not Answered

Updated 3/8/2014 4:57:34 AM

1 Answer/Comment

(5x2 + 2x - 3)(x - 1)

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 3/8/2014 4:57:32 AM

This answer has been confirmed as correct and helpful.

Find the product.
(n^3)^2 · (n^5)^4

Question

Not Answered

Updated 5/19/2014 5:56:21 AM

1 Answer/Comment

(n^3)^2 · (n^5)^4;

n^6 · n^20

= n^26

n^6 · n^20

= n^26

Added 5/19/2014 5:56:21 AM

This answer has been confirmed as correct and helpful.

27,678,467

questions answered

There are no comments.